How China’s State Actors Create a “Us vs US” World during Covid-19 Pandemic on Social Media - Xin Zhao (Media and Communication, 2020)
Health and science controversies surrounding Covid-19 pandemic have been politicized by state actors to manipulate international relations and politics. China is no exception. Using a package of communication tactics, the Chinese government has been engaging in an English-language information campaign to create an “Us vs US” world during the pandemic on social media. While the world is scrutinizing the accuracy of and the intention behind the information disseminated by China’s state actors, this commentary urges scholars to also focus on the influence of such information on global audiences, as well as on global power dynamics.